2012
DOI: 10.1016/j.lfs.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic properties of SOL1: A novel dual inhibitor of neutral endopeptidase and endothelin converting enzyme

Abstract: These data indicate that SOL1 is primarily a NEP inhibitor in vitro as well as in vivo. Given the preferential renal accumulation and renal clearance of SOL1 additional ECE-1 inhibition in the kidney may have contributed to its chronic BP lowering effects in the DOCA-salt hypertensive rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…To evaluate this, we treated adult SHR with the dual NEP/ECE inhibitor SOL1, which effectively decreases big-ET-1 to ET-1 conversion, 34 and compared the effects with a 4-week treatment with an AT 1 receptor antagonist (losartan) and a 4-week treatment with a vasodilator (hydralazine). Decreasing ET-1 production might be helpful in conditions where either the intravascular levels of ET-1 and/or the vascular effects of the peptide are increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate this, we treated adult SHR with the dual NEP/ECE inhibitor SOL1, which effectively decreases big-ET-1 to ET-1 conversion, 34 and compared the effects with a 4-week treatment with an AT 1 receptor antagonist (losartan) and a 4-week treatment with a vasodilator (hydralazine). Decreasing ET-1 production might be helpful in conditions where either the intravascular levels of ET-1 and/or the vascular effects of the peptide are increased.…”
Section: Discussionmentioning
confidence: 99%
“…This means that both EDNO-and EDHF-type responses in the SOL1-treated group were improved by acute ET-receptor antagonism. Because SOL1 is easily removed from organs, 20 conversion of big-ET-1 to ET-1 may recommence before endothelial function is investigated. Subsequently, ET-1 might impair endothelium-derived relaxing responses through a similar myo-endothelial coupling mechanism, as proposed by Hilgers and De Mey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary dose-finding experiments were carried out to identify appropriate doses of the dual NEP/ECE inhibitor SOL1 (2- 25 ). A dose of 50 mg kg À1 per day drastically decreased urinary ET1 content (from 32.89±3.91 to 1.35±0.25 pg ml À1 , Po0.001) in DOCA-salt hypertensive rats (n ¼ 3).…”
Section: Animals Model and Surgerymentioning
confidence: 99%
“…[22][23][24] Thus, a dual inhibitor of NEP and ECE reduces ET1 production by inhibiting all three pathways. 25 Recently Kalk et al 26 reported that the dual NEP/ECE inhibitor SLV338 reduces smooth muscle hypertrophy, interstitial fibrosis and perivascular fibrosis in the two kidney one clip model, partly by suppression of TGF-b1 expression.…”
Section: Introductionmentioning
confidence: 99%